How to Do Research in Science and Engineering Education: A Methodological Framework with Lessons Learned from Common Research Failures, Bibliometric Analysis, and Practical Insights - Aay Susilawati; Sri Rosalin Nandiyanti; Noor Azwadi Che Siddik; Asep Bayu Dani Nandiyanto (Bumi Publikasi Nusantara, 2025)
This paper presents a practical guide for improving research quality in science and engineering education based on lessons learned from real manuscript revision processes. Although many researchers aim to conduct studies in this field, research quality is often weakened by misalignment between stated scope, scientific content, engineering processes, and methodological descriptions. This study analyzes several research manuscripts that underwent academic coaching and were successfully revised and published in reputable journals, completed with a bibliometric analysis. Research quality can be significantly improved without altering core research designs, but through clearer articulation of scientific concepts, explicit description of engineering or technological interventions, and stronger alignment between methodology and research objectives. This paper offers actionable and experience-based guidance for researchers seeking to produce more rigorous, coherent, and impactful studies in science and engineering education.